“I’m Just a Cowboy”: Transnational Identities of the Borderlands in Tommy Lee Jones’ The Three Burials of Melquiades Estrada. - Matthew Carter (European Journal of American Studies)
As a problematic in-between space of racial antagonisms, liminal identities, and violence, the borderlands of the American Southwest prove fertile grounds for scrutinising Anglo-America’s national frontier mythology and, therefore, its own sense of history and cultural identity. This article explores the extent to which the “contemporary” border Western, The Three Burials of Melquiades Estrada (2005),challenges Hollywood’s cinematic hegemony in this regard. It argues that with Three Burials comes a sophisticated challenge to the cinema’s characteristic and mythic forms and to the racial assumptions that have traditionally bedevilled relations between Mexico and the USA. Transnational themes bring these issues to the fore and modify the terms in which they are represented and, therefore, imagined.